STUDIO INOVASI DAN KREATIF KERAJINAN KAYU - Triani, Joanne Triani; Choandi, Mieke (Jurusan Arsitektur dan Perencanaan, 2019)
Woodcrafts Innovation and Creative Studio are a place for craftsmen or enthusiasts of craftsmanship and process, especially wood. With four main programs: Experience, Explore & Learn, Develop, and Community, it’s expected to become a space for providing resources, facilities, knowledge and forming a community for people to work and create a variety of local products, as well as maintaining and contributing to creative economic growth. The background of this studio, because of the potential of natural resources and creative resources. Millennials' behavior differs from those of the previous generation, whereas millennials are perceived to be more creative, giving birth to many potentials in creative economy industry. Craft is one of the three industries who constitute the most contributions to the creative economy, namely woodcraft. Although potential, it's growth has shown to be stagnated, due to the difficulty to transfer of knowledge to the younger generation. For this reason, it’s necessary to provide a space that can introduce and become a forum to ensure the development of creative economy. Based on the results of some researches conducted on millennials, this generation has the desire to engage in new experiences and opportunities to meet people. This behavior can be used to offer a craft product with the addition of experience and stories that can attract millennials. Located in Kemang, which is known as an area that developed towards the artpreneur with the presence of various art store and galleries. This studio provides a space for experience seekers and creative industry players to share ideas, products, knowledge, and tools. The objective is so that those who do not have the skills yet can gain new experiences and skills, even explore the potential in the creative industry. As for creative economic actors, they can deepen their potential and share their knowledge. Aside from that, they can also market their products to a wider scope. AbstrakStudio kreatif dan inovasi kerajinan kayu merupakan wadah bagi pengrajin ataupun peminat ilmu dan keahlian dalam proses kerajinan, khususnya material kayu. Melalui empat program yaitu Experience, Explore & Learn, Develop, dan Community membentuk sebuah studio yang menyediakan sumber daya, fasilitas, pengetahuan, serta sebuah komunitas untuk berkarya melalui produk kerajinan kreatif berkelanjutan, dan mendorong pertumbuhan ekonomi kreatif khususnya kerajinan kayu. Latar belakang hadirnya studio ini, karena potensi sumber daya alam hingga sumber daya kreatif yang dimiliki di Indonesia. Generasi milinial dinilai lebih kreatif daripada generasi sebelumnya, ditandai dengan ekonomi kreatif baru diberbagai bidang. Ekonomi kreatif kerajinan merupakan salah satu bidang yang menyumbang perekonomian terbesar bagi negara. Kerajinan kayu memiliki potensi yang besar, namun pertumbuhannya mengalami stagnasi. Terhambatnya pertumbuhan diakibatkan kesulitan dan terbatasnya perpindahan ilmu ke generasi muda. Untuk itu wadah komunitas ini yang dapat mengenalkan ekonomi kreatif kepada millenial, agar generasi ini dapat terlibat pengalaman dan kesempatan bertemu sesama peminat ketrampilan kerajinan. Melalui riset terhadap generasi millenial, terdapat keinginan pada generasi ini untuk terlibat pengalaman. Perilaku ini dapat dimanfaatkan untuk menawarkan suatu produk kerajinan dengan penambahan pengalaman dan cerita didalam produk yang dapat menarik minat generasi millennial. Berlokasi di Kemang, Jakarta Selatan yang dikenal sebagai kawasan berkembang ke arah artpreneur , ditandakan banyaknya art store, galeri, dan lain-lain. Studio ini menjadi wadah untuk mendapatkan pengalaman dan menggali potensi dibidang ekonomi kreatif bagi pemula. Sedangkan untuk pelaku ekonomi kreatif dapat memperdalam potensi dan berbagi ilmu dalam proses kreatif, serta mendapat kesempatan berkolaborasi dan memasarkan hasil produk ke lingkup yang lebih luas.